Modeling seasonal detection patterns for burrowing owl surveys - Quresh S. Latif; Kathleen D. Fleming; Cameron Barrows; John T. Rotenberry (Wildlife Society Bulletin)
Abstract To guide monitoring of burrowing owls (Athene cunicularia) in the Coachella Valley, California, USA, we analyzed survey‐method‐specific seasonal variation in detectability. Point‐based call‐broadcast surveys yielded high early season detectability that then declined through time, whereas detectability on driving surveys increased through the season. Point surveys without call‐broadcasts yielded the lowest detectability rates overall. To maximize detectability, we recommend coupling early season point‐based call‐broadcast surveys with late‐season driving surveys. Occupancy models proved useful for integrating data from multiple methods to analyze distributional patterns while accounting for variation in detectability. © 2012 The Wildlife Society.